Versatile High-Throughput Platform for Focused Ultrasound In Vitro Application - Steffen H. Tretbar; Marc Fournelle; Christian Degel; Franz-Josef Becker; Peter Weber; Sarah Therre-Mohr; Wolfgang Bost; Lisa Landgraf; Andreas Melzer (Applied Sciences)
For the more efficient application of ultrasound in future therapies, fundamental research is needed on the mode of action of ultrasound on biological systems using therapeutic frequencies. To address this need, a new versatile high-throughput platform for focused ultrasound in vitro application was designed, developed, and characterized. The applicator was aligned with the dimensions of a 96-well plate and frequencies commonly used in the therapeutic ultrasound range (0.5–2.0 MHz). Two different platform configurations were developed: (a) a low-intensity version with 96 individual transducers allowing dry coupling of the well plate; and (b) a high-intensity version with water cooling, supporting parallel sonication of 32 out of 96 wells. The platforms were characterized by performing an analysis of the homogeneity of the sound pressure and intensity, the impact of filled volume per well, the cross-coupling effect between the wells, and the influence of the well plate. The low-intensity design delivers pressure levels up to 605 kPa inside the well with maximum ISPPA values between 0.78 and 12.38 W/cm2. In contrast, the high-intensity system achieves pressures up to 1460 kPa and a maximum ISPPA of 72 W/cm2 inside the wells. The successfully developed high-throughput platform supports parallelized sonication in standard, well-plate formats and is suitable for focused ultrasound applications in vitro.